Asymmetric finger-shape metallization in Graphene-on-Si solar cells for enhanced carrier trapping. (1st March 2019) - Pour-mohammadi, Zeinab; Amirmazlaghani, Mina
Abstract: Schottky junctions are promising structures for solar-to-electrical energy conversion. Using semi-transparent Graphene as the semi-metal in Graphene-on-Si Schottky solar cells has been highly regarded in recent years. In spite of introducing different methods to improve the solar characteristics of this structure, no idea for trapping the photo-generated carriers in Graphene layers is reported. Here, we propose an asymmetric interdigitated finger-shape metallization on Graphene layer in Graphene-on-Si Schottky solar cells to provide the possibility of carrier harvesting in Graphene layer. The unequal work function of asymmetric metallization can induce an internal electric field in Graphene layer. This electric field can be spread throughout the Graphene by the use of interdigitated finger-shape electrodes. The effect of using this structure on carrier trapping is investigated by simulation results and the experimental measurements. The reduced Graphene Oxide (rGO) has been chosen as the source of Graphene in our samples. The rectifying behaviour of the fabricated junctions has been studied by measuring the (current-voltage) characteristics. The Schottky barrier potential and the ideality factor have been measured in the range of (0.59–0.7) eV and (10.5–13.6) for our fabricated Schottky junctions, respectively. The solar characteristic of the fabricated junctions has also been tested under AM 1.5 solar illuminations. The measurement results show that the use of asymmetric finger-shape electrodes increase the short circuit current and the open circuit voltage by the factor of 2.5 and 1.25, respectively. The effect of GO density and the reduction method on solar characteristics have also been examined and presented.